2011
DOI: 10.4317/medoral.17306
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage comparison of glass-ionomer and white mineral trioxide aggregate used as a coronal barrier in nonvital bleaching

Abstract: Objectives: There is some evidence that the pH at the root surface is reduced by intracoronal placement of bleaching pastes, which is known to enhance osteoclastic activity. Therefore, it is recommended that a protective barrier be used over the canal filling to prevent leakage of bleaching agents. Glass-ionomer (GI) is commonly used as a coronal barrier before nonvital bleaching. Because mineral trioxide aggregate (MTA) creates high alkalinity after mixing with water, using MTA as a protective barrier over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
19
0
5
Order By: Relevance
“…With time, as the material sets, the concentration of calcium ions increases resulting in a mineralized dentin-MTA interstitial layer 6 which could have occluded the passage of hydrogen peroxide to the periodontium. An in-vitro study by Vosoughhosseini et al 7 showed white MTA had superior sealing property when used as a barrier material compared to GIC.…”
Section: Discussionmentioning
confidence: 99%
“…With time, as the material sets, the concentration of calcium ions increases resulting in a mineralized dentin-MTA interstitial layer 6 which could have occluded the passage of hydrogen peroxide to the periodontium. An in-vitro study by Vosoughhosseini et al 7 showed white MTA had superior sealing property when used as a barrier material compared to GIC.…”
Section: Discussionmentioning
confidence: 99%
“…The material evaluated by the push-out test and failure mode analysis can assess the dental bleaching materials effects on the cervical barrier with accuracy, in comparison to infiltration methods. 4,29,35,36 The cervical barrier using glass-ionomer cements may have different results depending on the bleaching agent chemical composition and/or application time at the cervical barrier of endodontically-treated teeth. However, future studies using the described methodology are needed to evaluate the best material for use as a cervical barrier in endodontically-treated teeth bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…The pH on the root surface is reduced after the use of endogenous bleaching agents. This acid medium appears to contribute to osteoclastic activity that will result in root resorption 21 . The lack of bond between the cement and enamel is a predisposing factor for the occurrence of external cervical resorption after endogenous bleaching, since it favors penetration of bleaching agents during the treatment 1,3,5,9 .…”
Section: Discussionmentioning
confidence: 99%